Payment for Environmental Services: offering smallholder famers a choice for sustainable change - Moreno, Alonso (CGIAR Challenge Program on Water and Food, 2009)
The Challenge Program on Water and Food project ‘Payment for environmental services as a mechanism for promoting rural development in the upper watersheds of the tropics’. This project locks at ways in which the negative affect of unsustainable land use can be minimized.in five Andean watersheds, it explore the feasibility of credit arrangement and direct payments to poor famers in the upper catchment to improve land use practice and family income. Credit provides poor famers with a choice to change agricultural practices that degrade water and soil and compromise the livelihood of communities living downstream. By recognizing the nature of the natural resource base as provide of environmental services, the project s liking the poor smallholder famer in the upper catchments with the beneficiaries of these services in lower catchments.